The performance of professionally-oriented and bureaucratically-oriented teachers in schools of different levels of perceived bureaucratization - Ramos, Herminia Cruz (1983)
This research sought to determine how teachers perceive their schools bureaucratic structures with respect to dimensions of centralization, job codification and formulation and how teachers perform in schools with varying levels of bureaucratization. The study had 100 teachers from 6 urban schools and 111 teachers from 5 rural schools from Cavite province as respondents. The highest levels that exist in the schools are in job codification; the lowest levels are in centralization. Teachers' orientation did not affect their perception of structures but professionally-oriented teacher's performance was a little higher than that of their bureaucratically-oriented counterparts.
Thesis (D.Ed.)--University of the Philippines, Diliman.
Keywords: Elementary school teachers -- Philippines -- Cavite; School management and organization -- Philippines -- Cavite